AIAA's 3rd Annual Aviation Technology, Integration, and Operations (ATIO) Forum 2003
DOI: 10.2514/6.2003-6758
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Scheduling Architecture for Multi-Center Time-Based Metering

Abstract: The Traffic Management Advisor (TMA) is an air traffic control automation system currently in use in seven Air Route Traffic Control Centers (ARTCCs) to enable time based metering to busy airports within their airspace. However, this system is limited to operation within a single ARTCC, within about a 200 nautical mile radius of the airport, and on relatively simple streams of traffic. The need for coordinated metering within a greater (300+ nautical mile) radius of an airport, on streams of traffic with signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…13 The initial condition was selected at a corresponding track point. For flights following shorter arrival routes from the north and the south, the first track point in the Center was selected.…”
Section: Vb Route and Vertical Profilementioning
confidence: 99%
See 1 more Smart Citation
“…13 The initial condition was selected at a corresponding track point. For flights following shorter arrival routes from the north and the south, the first track point in the Center was selected.…”
Section: Vb Route and Vertical Profilementioning
confidence: 99%
“…In the United States, the Traffic Management Advisor (TMA) 13,14 computes metering-fix scheduled times of arrival (STA) at the TRACON boundary in order to control throughput of en-route traffic arriving at a high-density airport. The Efficient Descent Advisor (EDA), which was developed to assist en-route controllers in achieving TMA's STAs while maintaining separation, computes clearance advisories that also enable fuel-efficient continuous descent arrivals (CDA).…”
Section: Introductionmentioning
confidence: 99%
“…A pilot-in-loop simulation study [2] conducted on a model of air traffic at the PHL airport has shown that instead of using a single large TMA-SC system with a 400 nm radius freeze horizon it is better to use two smaller TMA-SC systems: The inner system was designed to produce STAs at the runway and at metering points on the TRACON boundary, and had a 200 nm freeze horizon. The outer system was designed to produce STAs at the runway and metering points close to the boundaries between the ARTCCs surrounding the PHL airport and its freeze horizon was 400 nm from the runway.…”
Section: Proposed Structure Of the Airspace In The Vicinity Of An Airmentioning
confidence: 99%
“…A time-based strategic planning tool called Traffic Management Advisor Single Center (TMA-SC) is currently used at seven Air Route Traffic Control Centers (ARTCCs) to efficiently manage the flow of incoming aircraft to the airports within those ARTCCs [2] , and expansion to all 20 centers is planned by 2007. However, TMA-SC operates within a single ARTCC, and applying similar time-based metering at tightly constrained airports in the northeast corridor of the U.S., presents new challenges due to the nature of the airspace around these airports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation